القيم في برامج الأطفال في القنوات الفضائية الجزائرية قناة عمو يزيد أنموذجا - مولاتي نور الهدى (University of Eloued جامعة الوادي, 2024)
"تهدفت الدراسة إلى بيان القيم المتضمنة في برامج الأطفال الجزائرية وعلى وجه الخصوص قناة عمو يزيد، من خلال طرح الإشكالية المتمثلة في ماهي القيم التي تتضمنها قناة عمو يزيد الجزائرية الموجهة للأطفال؟. وللإجابة على هذا الإشكال ثم الاعتماد على العينة العشوائية البسيطة وعلى الأداة الاستبيان لجمع البيانات من أفراد مجتمع البحث البالغ عددهم 30 فرد، مما قسمنا الاستبيان إلى 04محاور. " The study aimed to clarify the values included in Algerian children's programs, especially the Amo Yazid channel, by raising the problem of: What are the values included in the Algerian Amo Yazid channel directed at children?. To answer this problem, we relied on a simple random sample and the questionnaire tool to collect data from the (30) members of the research community. We divided the questionnaire into (04) axes.
Keywords: القيم، برامج الأطفال التلفزيونية، قناة عمو يزيد; Values; children's TV programs; Amo Yazid channel